Islamic Political Parties in Contemporary Bangladesh: Paragons of Democratic Politics, or Rent-Seeking Parasites? - Bobby Hajjaj (Polit Journal Scientific Journal of Politics, 2022)
A variety of Islamic political parties proliferate the South and South-East Asian nations, most of which advocate a sharia-based form of government. This paper articulates the political participation of Islamic parties in Bangladesh and attempts to delineate the nature of their participation in more recent times. While Islamic political parties in Bangladesh fall between a range of political ideologies, their activities, especially their nature of participation in the 2018 general elections, were far removed from those stated ideologies and fell more in-line with exploitative rent-seeking models of politics.